SEDIMENTATION RATE AS DETERMINED BY 226RA ACTIVITY IN MARINE BARITE - Paytan A.; Moore W.S.; Kastner M. (My University, 1996)
In recently formed marine barite (BaSO4) separated from two equatorial Pacific cores 226Ra activity exceeds that of its parent 230Th by at least an order of magnitude, indicating radium uptake during barite precipitation. The decay of 226Ra with depth, in these samples, is exponential implying that no radium exchange with porewaters occurs after burial. Thus, barite behaves as a closed system below the sediment mixed layer. The absence of 226Raexs activity in barite samples older than ~8000 years, the lack of any detectable 228Th, 228Ra, and 224Ra in any of the barite samples analyzed, and the unaltered crystal size and habit with depth in the sediment, further support this conclusion. Hence, assuming that oceanic RaBa ratio has not changed throughout the Holocene, the decay of unsupported 226Ra permits dating of marine barite and estimating sedimentation rates. Holocene sedimentation rates calculated using the decay of 226Raexs in barite are consistent with 14C and δ18O derived sedimentation rates of 2-3 cm/kyr for the same cores. The method could be extendible to carbonate-poor Holocene sediments.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен